Lithium supplement material and preparation method thereof

By adopting spherical core-shell structure of lithium ferrous phosphate coated with lithium-rich lithium ferrate material, combined with tannin modification and carbon doping technology, the problems of poor conductivity and environmental instability of lithium-ion batteries are solved, and the comprehensive performance of lithium-ion batteries is significantly improved.

CN119695116APending Publication Date: 2025-03-25SHANDONG SACRED SUN POWER SOURCES
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411882578.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery lithium-enhancing materials have problems such as poor conductivity and environmental instability during use, which affects their wide application.

Method used

The lithium supplement material adopts a spherical core-shell structure. The outer layer is lithium ferrous phosphate and the inner layer is lithium lithium ferrate. It is modified and coated by tannin acid to form a stable and uniform interface structure, and amorphous carbon doped structure is formed through calcination to improve conductivity and ion diffusion rate.

Benefits of technology

It significantly improves the charge and discharge capacity of lithium-ion batteries, first-time Coulomb efficiency, rate performance and cycle stability, overcomes the problem of the increase in internal resistance of the original materials after the first charging and discharge, and reduces the sensitivity to environmental moisture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198554120000091
    Figure BDA0005198554120000091
  • Figure BDA0005198554120000101
    Figure BDA0005198554120000101
  • Figure HDA0005198554130000011
    Figure HDA0005198554130000011
Patent Text Reader

Abstract

The invention discloses a lithium supplementing material and a preparation method thereof, and belongs to the technical field of lithium ion battery lithium supplementing materials. The lithium supplementing material has a spherical core-shell structure; the spherical core-shell structure sequentially comprises a lithium iron phosphate layer and a lithium-rich lithium ferrite layer from outside to inside. The lithium supplementing material is prepared by two steps: firstly, carrying out surface coating in a similar sol-gel mode to obtain a material precursor, and then carrying out heat treatment on the precursor to obtain the lithium iron phosphate coated lithium-rich lithium ferrite material; in the preparation process, tannic acid is introduced for modified coating, so that the lithium iron phosphate coated lithium-rich lithium ferrite material which is uniformly coated and has high lithium supplement efficiency, high stability and relatively high reversible capacity is obtained, and the prepared lithium supplement agent material shows excellent lithium supplement performance and charge-discharge performance in a lithium ion battery performance test. Meanwhile, the preparation method is simple to operate and beneficial to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery lithium-supplementing materials, and in particular to a lithium-supplementing material and a preparation method thereof. Background Art

[0002] During the first charge and discharge process of lithium-ion batteries, the electrolyte undergoes a redox reaction on the surface of the electrode material (especially the negative electrode material), forming a passivation film (SEI film) covering the surface of the electrode material. The formation of the SEI film will inevitably consume some lithium ions, causing the loss of reversible lithium ions, thereby reducing the reversible capacity and energy density of the battery. When the active material of the negative electrode material is graphite, the SEI film formed will consume 5% to 15% of the reversible lithium ions, especially when the active material in the negative electrode sheet is silicon material, the consumption is more obvious (up to 20% or more). In order to effectively improve the energy density of the battery, the development of lithium supplementation technology is particularly important.

[0003] In order to increase the number of active lithium ions in the entire battery, pre-lithiation can be performed on different battery components, positive electrodes or negative electrodes, or on different levels, materials or electrodes, depending on the pre-lithiation method. However, there are still few lithium supplementation technologies used in commercialization, and there are some difficulties in the commercialization of lithium supplementation technologies.

[0004] Lithium iron-rich lithium Li5FeO4 is a high-capacity positive electrode lithium supplement additive, but this reagent reacts with moisture and carbon dioxide in the air to cause the material itself to be delithiated, resulting in the need to avoid contact with air as much as possible during use, which seriously affects the widespread use of such additives. Therefore, people have developed carbon-coated lithium iron-rich positive electrode lithium supplement materials or lithium iron phosphate / carbon / lithium iron-rich lithium composite positive electrode materials to solve the difficulties faced when using the above-mentioned Li5FeO4. Among them, the lithium iron phosphate / carbon / lithium iron-rich lithium composite positive electrode material described in CN118206093A is to use organic potassium or sodium salt as a carbon source, and then mix it with other raw materials and dry it to form a lithium iron phosphate / lithium iron-rich lithium precursor, and then perform high-temperature carbonization to decompose and dehydrogenate the carbon source, and use the principle of high-temperature self-activation of the carbon source to form porous carbon, and the carbon generated in situ is evenly coated on the surface of lithium iron phosphate and lithium iron-rich lithium, and the in-situ carbon can inhibit the growth of particles and alleviate the particle agglomeration phenomenon. The hydrogen gas released plays a certain role in pore formation, and combined with other precipitated gases, effectively increases the specific surface area of ​​the composite positive electrode material, thereby optimizing the pore structure of the composite positive electrode material, and obtaining a lithium-rich composite positive electrode material with a higher lithium content. However, the lithium iron phosphate / carbon / lithium-rich lithium ferrate composite positive electrode material can only be simply composited, and cannot form a composite material with uniform size and good coating, and cannot achieve the purpose of improving the performance of the lithium supplement agent. In addition, when preparing the lithium iron phosphate / carbon / lithium-rich lithium ferrate composite positive electrode material, a higher temperature is required for carbonization, and the amount of raw lithium compound used is large, which is not conducive to low-cost large-scale industrial production.

[0005] Therefore, researching and developing a new type of lithium replenishing material with high lithium replenishing efficiency and good environmental stability is of great significance for improving the charge and discharge capacity of lithium-ion batteries. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a lithium supplement material and a preparation method thereof. The lithium supplement material has excellent lithium supplement efficiency, and its application in lithium-ion batteries can significantly improve the battery's charge and discharge capacity, first coulomb efficiency, and rate performance.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a lithium supplement material having a spherical core-shell structure;

[0009] The spherical core-shell structure comprises a lithium iron phosphate layer and a lithium ferrite-rich lithium layer from the outside to the inside.

[0010] The lithium-supplementing material has a shell layer of a lithium iron phosphate layer and a core layer of a lithium-rich lithium ferrate layer; the modified lithium-supplementing material can overcome the influence of the increased internal resistance caused by the poor conductivity of the residual LiFeO2 substance in the lithium-rich lithium ferrate material after the first charge and discharge; after the surface is coated with lithium iron phosphate, the sensitivity of the lithium-rich lithium ferrate material to moisture in the environment is reduced, which greatly improves the usability of the material.

[0011] The core-shell structure lithium-supplementing material described in the present invention is modified and coated with tannic acid. On the one hand, the tannic acid and the iron ions on the surface of the lithium-rich ferrite are complexed, so that a strong complex ion layer is formed on the surface of the lithium-rich ferrite layer, thereby forming a stable and uniform interface structure; on the other hand, tannic acid, as an organic carbon source, forms amorphous carbon after calcination and enters the lattice gaps of lithium ferrous phosphate and tannic acid-modified lithium-rich ferrite, which promotes electron conduction and the migration of lithium ions in the diffusion channel, and significantly improves the conductivity and ion diffusion rate of the material described in the present invention.

[0012] Preferably, in the present invention, the diameter of the lithium supplementing material is 3.5-4.5 μm, and more preferably 4 μm.

[0013] The thickness of the carbon-doped lithium iron phosphate layer is 300-400 nm, and more preferably 350 nm.

[0014] The present invention also provides a method for preparing the above-mentioned lithium supplement material, comprising the following steps:

[0015] (1) dispersing an iron source, a phosphorus source, tannic acid and lithium-rich lithium ferrite in a first organic solvent to obtain a S1 mixed solution;

[0016] (2) dissolving the lithium source in a second organic solvent to obtain a S2 mixed solution;

[0017] (3) adding the S2 mixed solution dropwise to the S1 mixed solution and stirring to obtain the S3 mixed solution, reacting, adjusting the pH after the reaction, and freeze-drying to obtain a lithium iron phosphate-coated lithium iron-rich material precursor;

[0018] (4) calcining the lithium iron phosphate coated lithium rich ferrite material precursor to obtain the lithium iron phosphate coated lithium rich ferrite material.

[0019] The calcination atmosphere is an inert atmosphere.

[0020] The inert atmosphere is a nitrogen atmosphere or a rare gas atmosphere.

[0021] Preferably, the mass ratio of tannic acid to lithium-rich ferrite is (0.5-3): 1. In some specific embodiments of the present invention, it is preferably 0.5: 1 or 0.75: 1 or 1: 1 or 1.25: 1 or 1.5: 1 or 1.75: 1 or 2: 1 or 2.25: 1 or 2.5: 1 or 2.75: 1 or 3: 1. Within the above mass ratio range, the preparation method can generate a core-shell structure with uniform size and uniform coating, thereby better improving the conductivity of the material and significantly improving the overall performance of lithium-ion batteries.

[0022] Preferably, the mass ratio of the tannic acid to the iron element in the iron source is (1.4-8.4): 1. In some specific embodiments of the present invention, it is preferably 1.4: 1 or 2.1: 1 or 2.8: 1 or 3.5: 1 or 4.2: 1 or 4.9: 1 or 5.6: 1 or 6.3: 1 or 7: 1 or 7.7: 1 or 8.4: 1. Within the above mass ratio range, when generating lithium iron phosphate material, it can play a good role in interstitial doping of carbon elements, which helps to improve electronic conduction and migration of lithium ions in diffusion channels, thereby improving the electrochemical performance of the lithium ion battery prepared subsequently.

[0023] In the above preparation method, the iron element in the iron source, the phosphorus element in the phosphorus source, the lithium element in the lithium source and the concentration of the dispersed substance in the mixed system will affect the uniformity of the core-shell structure.

[0024] Preferably, in the present invention, the molar ratio of the iron element in the iron source, the phosphorus element in the phosphorus source and the lithium element in the lithium source is 1:1:1.

[0025] Preferably, the mass concentration of the dispersed substance in the S1 mixed solution is 0.24-0.36 g / mL. In some specific embodiments of the present invention, it is preferably 0.3 g / mL.

[0026] Preferably, the mass concentration of the dispersed substance in the S2 mixed solution is 0.014-0.028 g / mL, and preferably 0.022 g / mL in some specific embodiments of the present invention.

[0027] Preferably, the iron source is selected from one or more of ferrous oxide, ferrous phosphate, ferrous oxalate, ferrous sulfate and ferrous chloride;

[0028] Preferably, the phosphorus source is selected from one or more of diammonium phosphate, ammonium phosphate, diammonium hydrogen phosphate, and potassium dihydrogen phosphate;

[0029] Preferably, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide and lithium acetate;

[0030] Preferably, the first organic solvent and the second organic solvent are independently selected from one or more of ethanol, ethylene glycol, glycerol and tetrahydrofuran.

[0031] The structural formula of the lithium-rich ferrite material is Li5FeO4. In the preparation method of the present invention, the hydroxyl group in the organic solvent is conducive to the tannic acid to better modify the lithium-rich ferrite and lithium iron phosphate, thereby improving the performance of the lithium supplement material.

[0032] Preferably, in the step (3), the stirring time is 0.5-2.5h; and / or, in the step (3), concentrated ammonia is used to adjust the pH to 8-9, and freeze-drying is performed under vacuum conditions; and / or, in the step (4), the calcination temperature is 400°C-500°C, the heating rate is 1-2°C / min, and the calcination time is 2.5-3.5h.

[0033] The pH value is preferably 8-9 in order to form a uniform coating layer.

[0034] The lithium supplement material precursor is obtained through the above post-treatment, and then calcined under inert atmosphere to form the lithium supplement material with a core-shell structure.

[0035] The lithium-rich lithium ferrate material provided by the present invention can be prepared by oneself or purchased.

[0036] The method for making the lithium-rich lithium ferrite material comprises the following steps:

[0037] (1) Fe2O3, LiOH and an organic solvent are dispersed by ball milling and dried to obtain a precursor;

[0038] (2) The obtained precursor is calcined in an oxygen atmosphere to obtain the product lithium iron oxide material Li5FeO4.

[0039] Preferably, the molar ratio of Fe2O3 to LiOH is 1:10.1;

[0040] Preferably, the organic solvent is ethanol.

[0041] The suspension is obtained through ball milling dispersion, and a powdery mixed material precursor is obtained through filtering, washing and drying.

[0042] The present invention has no particular limitation on the above-mentioned filtering, washing and drying methods, which are methods well known to those skilled in the art. In some specific embodiments of the present invention, the drying temperature is preferably 60° C., and the drying time is preferably 9-12 hours.

[0043] Then, the precursor is calcined in an oxygen atmosphere to obtain the Li5FeO4 material.

[0044] The calcination temperature is preferably 1000-1100°C.

[0045] The heating rate of the calcination is 1-2°C / min, and the holding time is 20-30h.

[0046] The oxygen flow rate of the calcination is 0.1-0.2 L / min.

[0047] After the calcination is completed, ball milling is also included.

[0048] In the above-mentioned homemade method, the revolution speed of the ball milling dispersion in step (1) and the ball milling treatment after the calcination in step (2) are independently 300-400 rpm, the rotation speed is independently 500-600 rpm, and the ball milling time is independently 30-60 min.

[0049] The present invention further provides a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises the above-mentioned lithium supplement material or the lithium supplement material prepared by the above-mentioned preparation method.

[0050] Preferably, the positive electrode of the lithium-ion battery further includes a conductive agent, an adhesive, and the like.

[0051] Preferably, the mass ratio of the lithium supplement material, the conductive agent and the adhesive in the lithium ion battery is 90:5:5.

[0052] The conductive agent includes but is not limited to acetylene black, and the adhesive includes but is not limited to polyvinylidene fluoride.

[0053] The preparation of the positive electrode sheet comprises the following steps: the lithium supplement material, conductive agent, adhesive and N-methylpyrrolidone of the present invention are mixed evenly and then coated on aluminum foil, followed by drying, assembling and pressing to obtain a positive electrode sheet.

[0054] The negative electrode sheet is preferably made of metallic lithium.

[0055] The electrolyte is preferably a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) of lithium hexafluorophosphate.

[0056] Compared with the prior art, the lithium supplement material provided by the present invention has a spherical coating structure; the spherical core-shell structure is a lithium iron phosphate layer and a lithium iron-rich layer from the outside to the inside; the core layer is a lithium iron-rich layer, and the shell layer is lithium iron phosphate. The lithium supplement material is coated with lithium iron phosphate so that it has both excellent lithium supplement efficiency and good environmental stability. Its application in lithium-ion batteries can significantly improve the battery's charge and discharge capacity, first coulomb efficiency, rate performance and cycle stability. In addition, the lithium supplement material is prepared in two steps. First, a material precursor is obtained by surface coating in a sol-gel manner, and then the precursor is heat-treated to obtain a lithium iron phosphate-coated lithium iron-rich material; tannic acid is introduced for coating during the preparation process, thereby obtaining a lithium iron phosphate-coated lithium iron-rich material with uniform coating, high lithium supplement efficiency, high stability and high reversible capacity. The prepared lithium supplement material exhibits excellent lithium supplement performance and charge and discharge performance in lithium-ion battery performance tests. At the same time, the preparation method of the present invention is simple to operate and is conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a schematic diagram of the structure of the lithium supplement material prepared in Example 1. DETAILED DESCRIPTION

[0058] In order to further illustrate the present invention, the lithium supplement material and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples.

[0059] The lithium-rich lithium iron oxide materials used in the embodiments and comparative examples of the present invention are all homemade, and the homemade method comprises the following steps:

[0060] (1) Weigh a certain mass of Fe2O3 and LiOH in a molar ratio of 1:10.1, dissolve them in 80 mL of ethanol and stir evenly to obtain a mixed solution.

[0061] (2) The mixed solution was dispersed in a ball mill at a revolution speed of 300 rpm and a rotation speed of 500 rpm for 30 minutes, and the slurry was dried in an oven at 60° C. for 6 hours to obtain a powdery mixed material.

[0062] (3) The obtained powdered mixture precursor is placed in a tubular furnace and calcined at 1000°C for 20 hours under oxygen atmosphere conditions (oxygen flow rate is 0.1 L / min) with a heating rate of 1°C / min. After sintering, the furnace is cooled to room temperature; the obtained product is ball-milled at an orbital speed of 300 rpm and a rotation speed of 500 rpm for 30 minutes to obtain a lithium-rich lithium ferrate material.

[0063] Example 1

[0064] The preparation method of lithium iron phosphate coated lithium-rich lithium ferrate material comprises the following steps:

[0065] (1) Weigh tannic acid (1.0 g), FeSO4·7H2O (2.78 g, 10 mmol), H3PO4 (0.98 g, 10 mmol), and 1.6 g of lithium-rich lithium ferrite and disperse them in 40 mL of ethanol to obtain a mixed solution S1;

[0066] (2) Weigh LiOH·H2O (0.42 g, 10 mmol) and dissolve it in 15 mL of ethylene glycol to obtain a S2 mixed solution;

[0067] (3) adding the S2 mixed solution to the S1 mixed solution at a rate of 1 mL / min and stirring, stirring for 1 h after the addition, to obtain a S3 mixed solution; wherein the molar ratio of lithium element in LiOH·H2O, iron element in FeSO4·7H2O, and phosphorus element in H3PO4 is Li:Fe:P=1:1:1;

[0068] (4) adding concentrated aqueous ammonia to the third mixed solution to adjust the pH value of the third mixed solution to 8-9, and performing vacuum freeze drying after the reaction to obtain a lithium iron phosphate-coated lithium iron-rich material precursor;

[0069] (5) The precursor is placed in a tube furnace and calcined at 500° C. for 3 h in an argon atmosphere at a heating rate of 1° C. / min to obtain a lithium-replenishing material with a spherical coating structure (core-shell structure).

[0070] Example 2

[0071] This embodiment provides a lithium supplement material, the only difference from Embodiment 1 is that ethanol is used instead of ethylene glycol in step (2).

[0072] Example 3

[0073] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of tannic acid used, which is 0.5 g.

[0074] Example 4

[0075] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of tannic acid used, which is 1.2 g.

[0076] Example 5

[0077] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of tannic acid used, which is 1.5 g.

[0078] Example 6

[0079] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of tannic acid used, which is 2.0 g.

[0080] Example 7

[0081] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of tannic acid used, which is 2.5 g.

[0082] Example 8

[0083] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of lithium-rich lithium ferrite used, which is 1.3 g.

[0084] Example 9

[0085] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of lithium-rich lithium ferrite used, which is 1.0 g.

[0086] Example 10

[0087] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of lithium-rich lithium ferrite used, which is 1.9 g.

[0088] Embodiment 11

[0089] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is the amount of lithium-rich lithium ferrite used, which is 2.2 g.

[0090] Example 12

[0091] This embodiment provides a lithium supplement material. The only difference from Embodiment 1 is that the addition amounts of LiOH·H2O and H3PO4 are changed so that the molar ratio of lithium element in LiOH·H2O, iron element in FeSO4·7H2O, and phosphorus element in H3PO4 is Li:Fe:P=0.8:1:0.8.

[0092] Embodiment 13

[0093] The embodiment of the present invention provides a lithium supplement material, the only difference from embodiment 1 is that the addition amounts of LiOH·H2O and H3PO4 are changed so that the molar ratio of lithium element in LiOH·H2O, iron element in FeSO4·7H2O, and phosphorus element in H3PO4 is Li:Fe:P=1.2:1:1.2.

[0094] Comparative Example 1

[0095] This comparative example provides a lithium iron phosphate coated lithium iron rich material, and the preparation method of the lithium iron phosphate coated lithium iron rich material comprises the following steps:

[0096] (1) FeSO4·7H2O (2.78 g, 10 mmol), H3PO4 (0.98 g, 10 mmol), and 1.6 g of lithium-rich lithium ferrite were weighed and dispersed in 40 mL of ethanol to obtain a first mixed solution;

[0097] (2) Weigh LiOH·H2O (0.42 g, 10 mmol) and dissolve it in 15 mL of ethylene glycol to obtain a second mixed solution;

[0098] (3) adding the second mixed solution to the first mixed solution at a rate of 1 mL / min and stirring, stirring for 1 h after the addition, to obtain a third mixed solution; wherein the molar ratio of lithium element in LiOH·H2O, iron element in FeSO4·7H2O, and phosphorus element in H3PO4 is Li:Fe:P=1:1:1;

[0099] (4) adding concentrated aqueous ammonia to the third mixed solution to adjust the pH value of the third mixed solution to 8-9, and performing vacuum freeze drying after the reaction to obtain a lithium iron phosphate-coated lithium iron-rich material precursor;

[0100] (5) The precursor was placed in a tubular furnace and calcined for 3 h at a temperature of 500 °C in an argon atmosphere at a heating rate of 1 °C / min to obtain an unevenly coated lithium supplement material.

[0101] Comparative Example 2

[0102] This comparative example provides a lithium-rich lithium iron oxide material, and the preparation method of the lithium-rich lithium iron oxide material comprises the following steps:

[0103] (1) Weighing 1.0 g of tannic acid and 1.6 g of lithium-rich lithium iron oxide material and dispersing them in 40 mL of ethanol to obtain a first mixed solution;

[0104] (2) adding concentrated ammonia water to the mixed solution to adjust the pH of the mixed solution to 8-9, and performing vacuum freeze drying after the reaction to obtain a material precursor;

[0105] (3) The precursor was placed in a tubular furnace and calcined at 500°C for 3 h in an argon atmosphere at a heating rate of 1°C / min to obtain a carbon-coated lithium ferrite-rich material.

[0106] Comparative Example 3

[0107] This comparative example provides a lithium iron phosphate material, and the preparation method of the lithium iron phosphate material comprises the following steps:

[0108] (1) Weigh tannic acid (1.0 g), FeSO4·7H2O (2.78 g, 10 mmol), and H3PO4 (0.98 g, 10 mmol) and disperse them in 40 mL of ethanol to obtain a first mixed solution;

[0109] (2) Weigh LiOH·H2O (0.42 g, 10 mmol) and dissolve it in 15 mL of ethylene glycol to obtain a second mixed solution;

[0110] (3) adding the second mixed solution to the first mixed solution at a rate of 1 mL / min and stirring, stirring for 1 h after the addition, to obtain a third mixed solution; wherein the molar ratio of lithium element in LiOH·H2O, iron element in FeSO4·7H2O, and phosphorus element in H3PO4 is Li:Fe:P=1:1:1;

[0111] (4) adding concentrated aqueous ammonia to the third mixed solution to adjust the pH value of the third mixed solution to 8-9, and performing vacuum freeze drying after the reaction to obtain a lithium iron phosphate material precursor;

[0112] (5) The precursor is placed in a tubular furnace and calcined at 500° C. for 3 h in an argon atmosphere at a heating rate of 1° C. / min to obtain a carbon-coated lithium iron phosphate material.

[0113] The performance tests of the materials prepared in Examples 1-13 and Comparative Examples 1-3 are as follows:

[0114] The prepared materials were made into button cells for electrochemical performance testing of lithium-ion batteries. The specific steps were as follows: the prepared materials, conductive agent acetylene black and adhesive polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a ratio of 90:5:5, and then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, the battery was assembled in an argon glove box and pressed into positive electrode sheets using a tablet press. The negative electrode was a metal lithium sheet, the electrolyte was 1M LiPF6-EC:DMC (the volume ratio of EC and DMC was EC:DMC=1:1), and a polypropylene porous membrane was used as a diaphragm. In the voltage range of 2.5-4.2V, the electrochemical performance was tested using constant current and constant voltage charging and constant current and discharge. The results are shown in Table 1.

[0115] Table 1 Performance test results of materials prepared in Examples 1-13 and Comparative Examples 1-3

[0116]

[0117]

[0118] The results in Table 1 show that when the preparation method of the present invention is adopted, the modified lithium supplement material obtained in Example 1 has excellent charge and discharge performance, and the 0.1C charge capacity is 406.5 mAh / g. Since the surface is coated with lithium iron phosphate, reversible charge and discharge can be performed, wherein the first efficiency is 19.8%, the 0.1C discharge capacity is 80.5 mAh / g, and the 3C discharge capacity is 70.8 mAh / g, and the rate performance is excellent;

[0119] The results of Examples 1-2 show that the selection of organic solvents will affect the performance of lithium iron phosphate-coated lithium-rich lithium ferrate material.

[0120] The results of Example 1 and Examples 3-7 show that the amount of tannic acid used will also affect the performance of the material. When the mass ratio of the two is further selected within the scope of the present invention, the obtained lithium ion cycle performance and rate performance are more excellent. Specifically, the first efficiency is about 19.5%, the 0.1C charging capacity is above 400mAh / g, the 0.1C discharge capacity is about 80mAh / g, and the 3C discharge capacity is above 70mAh / g. When tannic acid is not introduced during the preparation process of Comparative Example 1, the charging capacity of the lithium ion battery prepared by the obtained coating material is significantly reduced, and the discharge performance and rate performance also show a significant downward trend, indicating that tannic acid has an important influence on the coating structure.

[0121] The results of Example 1 and Examples 8-11 show that the amount of lithium-rich lithium ferrite can adjust the initial efficiency and charge-discharge capacity of the obtained coating material, and a modified lithium supplement material with desired performance can be obtained.

[0122] The results of Example 1 and Examples 12-13 show that the Li:Fe:P element ratio will also affect the performance of the obtained coating material.

[0123] By comparing the results of Example 1 and Comparative Example 2, it is shown that when the outer layer of the material is not coated with lithium iron phosphate, the actual charging capacity (0.1C charging capacity) of the lithium ion battery prepared by the obtained lithium-rich lithium iron oxide material is 630.7 mAh / g, showing a significant downward trend (calculated, the charging capacity of the lithium-rich lithium iron oxide in Example 1 is 650.8 mAh / g), indicating that the surface coating of lithium iron phosphate layer is better than the simple coating of carbon layer;

[0124] It can be seen from Comparative Example 3 that the obtained lithium iron phosphate material also exhibits good charge and discharge performance, indicating that the surface coating layer of the coated structure lithium supplement material prepared by this method has excellent performance.

[0125] The lithium supplement material of the present invention has excellent performance, and has high lithium supplement efficiency, good charge and discharge performance, high stability and high reversible capacity, which can significantly improve the reversible capacity and energy density of lithium-ion batteries. In addition, the preparation method is simple to operate and suitable for large-scale industrial production. The modified lithium supplement material prepared by the method of the present invention is uniformly coated.

[0126] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A lithium supplement material, characterized in that: It has a spherical core-shell structure; The spherical core-shell structure comprises a lithium iron phosphate layer and a lithium ferrite-rich lithium layer from the outside to the inside.

2. The lithium supplement material according to claim 1, characterized in that: The diameter of the lithium supplement material is 3.5-4.5 μm; The thickness of the lithium iron phosphate layer is 300-400 nm.

3. The method for preparing the lithium supplement material according to claim 1 or 2, characterized in that: The following steps are involved: (1) dispersing an iron source, a phosphorus source, tannic acid and lithium-rich lithium ferrite in a first organic solvent to obtain a S1 mixed solution; (2) dissolving the lithium source in a second organic solvent to obtain a S2 mixed solution; (3) adding the S2 mixed solution dropwise to the S1 mixed solution and stirring to obtain the S3 mixed solution, reacting, adjusting the pH after the reaction, and freeze-drying to obtain a lithium iron phosphate-coated lithium iron-rich material precursor; (4) calcining the lithium iron phosphate coated lithium rich ferrite material precursor to obtain the lithium iron phosphate coated lithium rich ferrite material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the tannic acid to the lithium-rich lithium ferrite is (0.5-3):

1.

5. The preparation method according to claim 3, characterized in that: The mass ratio of the tannic acid to the iron element in the iron source is (1.4-8.4):

1.

6. The preparation method according to claim 3, characterized in that: The molar ratio of the iron element in the iron source, the phosphorus element in the phosphorus source and the lithium element in the lithium source is 1:1:

1.

7. The preparation method according to claim 3, characterized in that: The mass concentration of the dispersoid in the S1 mixed solution is 0.24-0.36 g / mL; the mass concentration of the dispersoid in the S2 mixed solution is 0.014-0.028 g / mL.

8. The preparation method according to claim 3, characterized in that: The iron source is selected from one or more of ferrous oxide, ferrous phosphate, ferrous oxalate, ferrous sulfate, and ferrous chloride; The phosphorus source is selected from one or more of diammonium phosphate, ammonium phosphate, diammonium hydrogen phosphate, and potassium dihydrogen phosphate; The lithium source is selected from one or more of lithium carbonate, lithium hydroxide and lithium acetate; The first organic solvent and the second organic solvent are independently selected from one or more of ethanol, ethylene glycol, glycerol, and tetrahydrofuran; The structural formula of the lithium-rich lithium ferrite material is Li5FeO4.

9. The preparation method according to claim 3, characterized in that: The stirring time in step (3) is 0.5-2.5h; and / or, concentrated ammonia water is used to adjust the pH to 8-9 in step (3), and freeze-drying is performed under vacuum conditions; and / or, the calcination temperature in step (4) is 400°C-500°C, the heating rate is 1-2°C / min, and the calcination time is 2.5-3.5h.

10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery comprises the lithium-supplementing material according to claim 1 or 2 or the lithium-supplementing material prepared by the preparation method according to any one of claims 3 to 9.

Citation Information

Cited By

  • Lithium-rich lithium ferrite lithium supplement agent as well as synthesis method and application thereof

    CN119905695A

  • Uniform multi-coated lithium supplement agent for in-situ generation of lithium iron phosphate as well as preparation method and application of uniform multi-coated lithium supplement agent

    CN120774395A

  • Composite material containing lithium supplement agent and lithium iron phosphate as well as preparation method and application of composite material

    CN120784330A